A Digital Juggling Act: New Media's Impact on the Responsibilities of Local Television Reporters. (March 2014) - Adornato, Anthony C.
Budding journalists entering the field, or those trying to stay relevant in their jobs, will have to be able to assume a range of job responsibilities in the evolving media landscape. This case study explores the dramatic transformation new media is having on the daily job responsibilities of local television journalists. Through in-depth interviews with reporters and direct observation at a television station in a medium-sized market, the research reveals reporters' tasks and work routines are evolving in three areas: dissemination, newsgathering, and the relationship with the audience. Study participants expected new media to impact their dissemination process, ramping up job demands as they produce content for multiple platforms. However, they never anticipated new media, particularly Facebook and Twitter, would be so useful in the newsgathering process. In addition, the research details how the shifting relationship with audience has affected reporters' responsibilities. Lessons learned from this research are helpful to others in the industry and journalism educators.